Examination of cross-functional activities facilitated by absolute value target costing and committee activities at Toyota Motor Corporation / Hideyuki Kobayashi - Hideyuki, Kobayashi (2014)
For many years, Toyota Motor Corporation has used variance from current cost as the basis for new part cost target setting. The incremental cost of the added specification is added to the current price of the part to establish a new cost target in variance-based target costing. Then by year 2000, Toyota switched to absolute value target costing that sets the target cost per vehicle by absolute value. The variance-based target costing was reasonable until 1990’s in Japan because suppliers of many parts were fixed and expenses other than design cost were relatively stable. However, it does not effectively work at overseas target costing because suppliers who have unique production processes or logistics may change at each model change. In addition to the change of target costing method, during this time, committees related to the cost became active and cross-functional activity was facilitated. Introduction of committee activities brought a change of development structure at Toyota from a matrix organization to three-dimensional structure. These changes in target costing brought about drastic changes as compared to previous few decades. In this article, the meaning and results of committee activity and effects brought by change of target setting method are described, as well as cross-functional activities facilitated by committee activities and absolute value target costing in order to clarify how they have contributed to the evolution of target costing at Toyota.